2017
DOI: 10.4028/www.scientific.net/ddf.378.113
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Non Newtonian Power-Law Fluid Flows and Mixed Convection Heat Transfer inside of Curved Duct

Abstract: A two-dimensional numerical simulation is carried out to understand the combined effects of thermal buoyancy strength and rheological flow behavior of non Newtonian power-law fluids on laminar flow and heat transfer rate through a 180° curved duct. The governing equations including the full Navier-Stokes, the continuity and the energy are solved using the commercial code ANSYS-CFX. The numerical results are presented and discussed for the range of conditions as: Re = 40 to 1000, Ri = 0 to 1 and n = 0.4 to 1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The forced and natural have an equal contribution of heat transfer at Ri = 1. Bouzit et al [17] simulated through two-dimensional numerical investigation the effect of thermal buoyancy and rheological flow behavior of non-Newtonian flow inside a curved channel the governing equations are solved with the range of following conditions: Re = 40 to 1000, Ri = 0 to 1 and n = 0.4 to 1.2 at fixed value of Prandtl number 0f Pr = 7. The results showed that some alternative vortices are seen to be appeared on duct walls and its number is seen to be increased with gradual increase in Richardson number as well as Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The forced and natural have an equal contribution of heat transfer at Ri = 1. Bouzit et al [17] simulated through two-dimensional numerical investigation the effect of thermal buoyancy and rheological flow behavior of non-Newtonian flow inside a curved channel the governing equations are solved with the range of following conditions: Re = 40 to 1000, Ri = 0 to 1 and n = 0.4 to 1.2 at fixed value of Prandtl number 0f Pr = 7. The results showed that some alternative vortices are seen to be appeared on duct walls and its number is seen to be increased with gradual increase in Richardson number as well as Reynolds number.…”
Section: Introductionmentioning
confidence: 99%